Intractable pain treated with intrathecal isotonic iced saline - Savitz, Martin H. (1973)
Hitchcock's original method of hypothermic subarachnoid irrigation employed both temperature and osmolarity. Spinal cooling was then abandoned in favour of intrathecal injection of normothermic hypertonic salilne. Modifications of the procedure that followed have continued to accept hyperosmolarity as the factor causing pain relief. Fifty patients were treated by a technique evolved to enhance the effect of hypothermia while avoiding the complications associated with hyperosmolar solutions. For the cases of terminal carcinoma and others considered to be poor surgical risks, the results have been quite satisfactory. For non-neoplastic painful syndromes, rapid perfusion cooling of the subarachnoid space offers an alternative therapeutic approach.